‘Should I stay or should I go?’: A mixed methods study on nurse retention during challenging times - Michael Joseph S. Diño; Paul John B. Bracero; Arnel Buencamino; Sharon B. Cajayon; Michael William Q. Catajan; Michaela Liel L. De Leon; Jessie Elsid Jr. Gregorio; Pamela Anne A. Lucelo; Bavy Charmy Cindy P. Odon; Jasmin Anne F. Palma; Roi Roel C. Rosado; Martin Phillip D. Taboada; Maria Luisa Uayan (Belitung Nursing Journal, 2022)
Background: The World Health Organization estimates that between 80,000 and 180,000 medical personnel perished as a result of COVID-19. Although studies about nurses’ organizational commitment during the COVID-19 pandemic have been conducted, the sources of motivations and resilience strategies of nurses in providing a quality healthcare service amidst the COVID-19 pandemic have yet to be explored. Objective: This study aimed to investigate how motivation and resilience influence nurses to serve and cater to patients during the COVID-19 pandemic.     Methods: A sequential exploratory mixed approach was used in this study between July and August 2022. The Connor-Davidson Resilience Scale (CD-RISC-10), Work Extrinsic and Intrinsic Motivations scale (WEIMS), and Garbee and Killacky’s Intent to Stay Scale (GKISS) were used to measure resilience, motivation, and intention to stay, among 50 nurses within Metro Manila. Quantitative data were analyzed using quantile regression, while qualitative data from eight participants were analyzed using thematic analysis. Results: The majority of the nurses were working 12 hours and above (52%) and earning a bi-weekly income of PHP 15,001 to 20,000 (96%). The GKISS scores of most respondents indicated their likelihood of remaining in their current profession was moderately low (Mdn = 12.5; IQR = 12-14). It was also found that there was no sufficient statistical evidence to conclude that intention to stay was associated with resilience (p = 0.914) and work motivation (p = 0.560). The qualitative strand of this study explored the significant influences of motivation, resilience strategies, and sources of intention to stay among Filipino nurses while facing the COVID-19 pandemic. The primary motivations of nurses lie in family, passion for work, and career development, while the resilience strategies include adaptiveness, time management skills, and self-fulfillments. On the other hand, the intent to stay greatly lies in serving the people and the country. Conclusion: This study concludes that positive and negative resilience and motivations from different facets of the social life of Filipino nurses, including passion, familial ties, patient care, and faith are the antecedents influencing the intention to serve in the healthcare service. In terms of staying for an extended period in a nursing career, the study found that institutionalized interventions, adequate compensation and benefits, and a good workplace are determinants of staying longer in the Philippines as Filipino nurses.